A study on cryogenically treated molybdenum wire electrode. (2021) - Myilsamy, Sureshkumar; Boopathi, S.; Yuvaraj, D.
Abstract: The molybdenum wire has been used as a cutting tool in the wire-cut electrical discharge machining process. In the cryo-cooled near-dry machining process, the cryo-cooled wire has been used as a cutting tool. In this paper, the hardness, electric conductivity, wear resistance, and surface microstructure of cryogenic treatment (immersed into liquid nitrogen) of molybdenum wire has been analyzed concerning the different cooling period. As per the literature survey, some investigations are required on the physical properties of Cyro-cooled molybdenum wire with lower temperature. The wire electrode was cryogenically treated by liquid nitrogen with one, two, and three hours of period. The specimens were initially prepared and dipped into liquid nitrogen in a Dewar's vessel for various time intervals and observe the physical properties modification. The hardness, electric conductivity, wear resistance, and microstructure of the cryogenically treated wires with untreated wire have been compared. It was observed that when the cooling period is increasing, then, the hardness, electric conductivity, wear resistance, and surface microstructure of wire have been improved.